"I just want to move forward": Themes of resilience among LGBTQ young adults experiencing family rejection and housing insecurity. (August 2022) - DeChants, Jonah P.; Shelton, Jama; Anyon, Yolanda; Bender, Kimberly
Highlights: LGBTQ young adults are at elevated risk of homelessness but also exhibit resilience. Anti-LGBTQ family rejection is one of the contributing factors of this elevated risk. Practices of resilience include strategizing, connecting, and coping. Practitioners working in housing programs should incorporate these practices to build resilience. Abstract: Lesbian, gay, bisexual, transgender, and queer or questioning (LGBTQ) young adults are overrepresented among young adults experiencing homelessness. Heterosexist and cisgenderist rejection from their families frequently causes and exacerbates this housing instability. Despite these challenges, LGBTQ young adults demonstrate tremendous resilience. Using grounded theory to analyze interviews with 15 young adults experiencing family rejection and housing instability, this study seeks to illuminate the practices and attitudes that allow LGBTQ young adults to develop and maintain resilience. Analysis of the interview data revealed three main themes: (1) strategizing: taking agency, making plans, and learning lessons; (2) connecting: getting support from individuals, institutions, and communities, and engaging in their own altruism; and, (3) coping: focusing on goals, maintaining motivation, and using creativity. This study holds important implications for housing agencies and others who seek to support LGBTQ young adults, suggesting that we should build programs that leverage the existing strengths and resilience of these young adults in efforts to create housing stability. ge the existing strengths and resilience of young adults in efforts to create housing stability.